Rondes de crème glacée virtuelles : Aborder le bien-être des stagiaires en médecine pendant la pandémie de COVID-19 - Kearney, Hannah; Lukings, Jorin (Revue canadienne de l'éducation médicale, 2020)
Ice Cream Rounds (ICRs) are used by residency and clerkship programs across Canada to provide trainees with a safe space to debrief difficult situations, connect with peers, and promote wellness. At the Niagara Regional Campus of the Michael G. DeGroote School of Medicine, ICRs are held often and are well-received by learners. In light of the COVID-19 pandemic, we adapted and facilitated the first virtual ICR. Post-session, students reported an increase in nearly all domains of their perceived wellness. Due to the uncertainty associated with this unprecedented time, this event could help learners at other institutions support each other.